The role of verbs in sentence depth (Raparin Journal of Humanities (RJH), 2024)
The research is devoted to investigate Sulaimani Central Kurdish dialect. The focus of the research is on Syntax and it is related to language meaning, because there is an overlap between Syntax and Semantics, the structure of Sentence has two sides, (Form and meaning), and verb as a main element of the Sentence plays a major role in sentence structuring.  The importance of this study is rely on the previous studies, some aspects of Kurdish Syntax have been applied to the branches of (GB) theories. This study is the use of another powerful aspect and connected theories to Kurdish Syntax that is the role and power of verb in Kurdish Syntax. At this level it is the division of meaning. Which gives Semantic roles to other phrases in the Sentence. Another side of verb role is demanding the necessary phrases, because they are used up to the verb demand. In other words, verb dominates both Syntactic and Semantic aspects of the sentence.